Correlation Analysis Among the Chemical Composition and Cytotoxic and Antioxidative Activities of a Tessaria absinthioides Decoction for Endorsing Its Potential Application in Oncology - Pascual, Lourdes Inés; Luna, Lorena Celina; Gonzalez, Roxana Elizabeth; Ortiz, Javier Esteban; Gomez Gomez, Luciano; Donadel, Osvaldo Juan; Hapon, María Belén; Feresin, Gabriela Egly; Gamarra Luques, Carlos Diego (MDPI, 2024)
Historically, botanical preparations have been used to improve human health. Their active ingredients are influenced by multiple factors such as intraspecies variations, environmental conditions, collection time and methods, and the part of the plant used. To ensure the efficiency and safety of these herbal drugs, qualitative and quantitative analyses are required. A Tessaria absinthioides decoction (DETa) was reported as having hypocholesterolemic, anti-inflammatory, cytotoxic, antitumor, and antioxidative properties. This work aimed to analyze DETa by correlating its chemical composition with cytotoxic and antioxidative properties, with the aim of promoting research on it as an anticancer agent. DETa collections (2017, 2018, 2019, and 2022) were analyzed by UHPLC-DAD, UHPLC-DAD-FLD, and UPLC-MS/MS; cytotoxicity was assessed on the MCF-7 breast cancer cell line; antioxidative capacity was evaluated by the DPPH and FRAP methods; and correlation analysis was used to determine biological and chemical markers. The results provide evidence that biological activities were consistent across the collections. Among the quantified compounds, apigenin, naringin, gallocatechin gallate, ginnalin A, myricetin, epicatechin, OH-tyrosol, quercetin, and chlorogenic, tessaric, p-coumaric, vanillic, caffeic, caftaric, ellagic, and rosmarinic acids correlated as bioactive and chemical markers. Moreover, tessaric acid could be established as a species marker. Altogether, these findings add relevant information to DETa properties, encouraging further exploration of its potential application as an anticancer botanical.